TRADISI DUTU PADA PERKAWINAN ADAT SUKU HULONDHALO DI KOTA GORONTALO PERSPEKTIF MAQĀSHID AL-SYARĪ’AH - Nurul Mahmudah; Supiah Supiah (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2018)
In Gorontalo city there is a tradition of dutu in his traditional marriage. This tradition certainly has philosophical reasons behind it, and one method of knowing the philosophy behind a rule is to use maqaid al-shari'ah al-Syaṭibi. The focus of this research is (1) How is the implementation of fiqh principles in the Hulondhalo tribe in the implementation of the tradition of dutu in customary marriage in the city of Gorontalo (2) How is the review of maqashid al-shari'ah on the tradition of traditional marriage dutu in the Hulondalo tribe in Gorontalo at a very expensive cost. This type of research is qualitative research, and the form of field research. The results of this study concluded that: (1) the implementation of the fiqh method was evidenced by the implementation of the tradition of the dutu whose procedure was to deliver 1 package of dowry and custom attributes delivered to the bride's house. For the tradition of dutu in the context of modernity, family position is a measure of the value of dowry for the bride and the social achievement of the woman. The higher the social value, the higher the value of the dowry. This is in accordance with the arguments of the hadith of the Prophet. (2) The review of maqashid al-shari'ah in this tradition includes the category of maqaṣid hajiyyat which safeguards maqaṣid dharuriyyatnya. Marriage as a form of hifz al-nasl which is commanded by Allah. The price of the dowry is in the position of ma'aid taḥsīniyyat to glorify a woman as a manifestation of maintaining religion, soul, mind, lineage, and wealth.